Common Grazing Resources of Hot Arid Zone of Rajasthan, India: Problems and Prospects - Misra, A K; Kumawat, R N (Annals of Arid Zone, 2021)
The agriculture in the hot arid zone of Rajasthan, India is mainly subsistence farming and pasturelands dominate among different land use systems. These lands provide main support to the huge livestock population of the region. About 60% of the total area of Rajasthan is arid where livestock rearing plays pivotal role in the economy and livelihood of the people. In arid region, animal husbandry sector provides round the year employment with more than 50% of total house hold income as against national average of 22.5%. Common Pool Resources (CPRs) or â€œcommonsâ€ are an important component of the agricultural production systems. The CPRs includes community pastures, community forests, government wastelands, common dumping and threshing grounds, river beds, watershed drainages, village ponds and rivers etc. In an estimate common pool comes to around 34.75% of the total geographical area of western Rajasthan. About half of this area is cultivable waste lands, 21% fallow lands (other than current fallow), 14% uncultivable waste lands, 11% permanent pastures and 7% is village forests. Common lands in arid Rajasthan were estimated to contribute 27.90% of dry fodder and 76.30% of green fodder requirement of the livestock in 1960 that decreased to 15.44% and 40.5%, respectively during 2012-13. Traditionally, a close link exists between crop, livestock and common grazing resources in the arid Rajasthan. This complex inter-relationship between CPRs, livestock and crops in arid land farming systems has contributed to the sustainability of dry land agriculture for generations. As the population of both animals and humans rises, there is a proportional increase in competition for food to feed the people that brings agriculture and livestock production into direct conflict. In the present article an attempt has been made to describe the extent and condition of common grazing lands, and examine the problems and prospects of these areas in changing agricultural scenario in hot arid zone of Rajasthan, India.Key words: Common pool resources, rangeland, orans, gauchars, productivity, management